Behind the Selling Price Determination in Commercial Photography Service Practice - Sugianto Sugianto (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
The photography industry is part of the creative economy, especially the process of determining the selling price of a product is the main focus of photographers in setting product prices. The study aims to determine the effect of value, profit, and cost on the practice of setting the selling price of products in the commercial photography business. It uses a qualitative approach with a netnographic method. The results of the study show that the determination of the selling price can be based on values ​​and culture, as well as the philosophy of thought that exists in society, where a phase in business is not always about profit, but more than that. It means that the profession is not only talking about profits, but how the profession is lived, enjoyed.